Global Liquidity : Credit and Funding Indicators. (Policy Papers; Policy Paper ;, 2013)
This note reviews some concepts of global liquidity and discusses measurement approaches that have been used by various interlocutors, including at the BIS, by Fund staff, and in academia. Some measures that could be regularly monitored by policy makers are presented.